Costs of reproduction are reflected in women's faces: Post‐menopausal women with fewer children are perceived as more attractive, healthier and younger than women with more children. Issue 3 (13th November 2017) - Marcinkowska, Urszula M.; Little, Anthony C.; Galbarczyk, Andrzej; Nenko, Ilona; Klimek, Magdalena; Jasienska, Grazyna
Abstract: Objectives: The costs associated with reproduction (i.e., gestation, lactation, childcare) have long‐term negative consequences by elevating risk of disease and reducing lifespan. We tested the hypotheses that high parity, and thus high reproductive costs bear by women, is perceived by other people when they evaluate facial appearance of health, attractiveness and age of mothers. Materials and Methods: Using computer software we created average facial images based on real photographs of post‐menopausal women with varying number of children; 3 parity categories were created (1–2, 4–5, and 7–9 children). Study participants ( N  = 571) were asked to choose the face they perceived as more attractive, younger and healthier via two‐alternative forced choice questions asked in three randomized blocks. Results: Women who had given birth to fewer children were judged both by men and women as more attractive, younger and healthier than women with more children. In each category the lowest scores were received by women from highest parity category (7–9 children). Discussion: Mechanisms behind the observed variation in facial appearance are not known but higher levels of oxidative stress among women with high parity may explain their faster aging and lower attractiveness in older age. These results suggest that costs of reproduction might affect women's physical appearance.